2015
DOI: 10.1017/s1751731115000476
|View full text |Cite
|
Sign up to set email alerts
|

Breeding objectives for sheep should be customised depending on variation in pasture growth across years

Abstract: Breeding programmes for livestock require economic weights for traits that reflect the most profitable animal in a given production system, which affect the response in each trait after selection. The profitability of sheep production systems is affected by changes in pasture growth as well as grain, meat and wool prices between seasons and across years. Annual pasture growth varies between regions within Australia's Mediterranean climate zone from low growth with long periods of drought to high growth with sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Given the climatic conditions, the western and eastern part of the Mediterranean could require a separate breeding program. This is comparable to the conclusion of Rose et al (2015) who demonstrated that sheep breeding programs in Australia should be region specific, depending on 97 pasture growth. For sea bass in Europe, most breeding programs include several traits in the breeding objective Janssen et al, In Press).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Given the climatic conditions, the western and eastern part of the Mediterranean could require a separate breeding program. This is comparable to the conclusion of Rose et al (2015) who demonstrated that sheep breeding programs in Australia should be region specific, depending on 97 pasture growth. For sea bass in Europe, most breeding programs include several traits in the breeding objective Janssen et al, In Press).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, it was valuable to decrease FCR whilst increasing TGC, which is easy to achieve when there are negative correlations between the two traits. The differences observed in genetic gain based on different EV have been shown to exist in terrestrial production systems Spelman and Garrick (1997) or Rose et al (2015). As expected, Differences in genetic gain across quota also generated differences in economic gains, suggesting that each quota would need a specific breeding program to maximize economic return for farmers and that using only one breeding goal with one set of EVs for all quotas would not be profitable for all farmers.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations